INCIDENTAL FINDINGS IN PANORAMIC RADIOGRAPHS: A DESCRIPTIVE STUDY OF PANORAMIC RADIOGRAPHS TAKEN ON X HOSPITAL IN JAMBI CITY INDONESIA - Pamadya, Sandy; Kurniati, Novi (Fakultas Kedokteran Gigi Unjani, 2025)
Abnormalities without symptoms can be detected through accurate diagnostic interpretation techniques in a wide range of panoramic radiographs. The number of publications describing various incidental findings on panoramic radiographs in Indonesia is still limited. The aim of this study is to find incidental findings in panoramic radiographs. The design of this study is descriptive, using 962 panoramic radiographs. A total of two observers interpreted 481 radiographs each and recorded incidental findings into five categories, namely soft tissue calcification, elongation of the styloid process, pathological conditions of the maxillary sinus, dense bone islands, and other incidental findings. The results shows that 142 panoramic radiographs (14,76%) had images of incidental findings, with descriptions of the types of incidental findings that were found are 42 radiographs (29,57%) of soft tissue calcification, 29 radiographs (20,42%) had an elongation of the styloid process, pathological conditions of the maxillary sinus were found on 35 radiographs (24,64%), 32 radiographs (22,53%) of dense bone island, and 17 radiographs (11,97%) were categorized as other incidental findings. The percentage of incidental findings which is not too high (14,76%), does not affect the fact that it is very important for a dentist to interpret panoramic radiographs in such detail manners and be alert of various pathological conditions that appear even without clinical symptoms, and ultimately be able to provide external referrals so that early medical intervention can be carried out in patients who needs it the most. DOI : 10.54052/jhds.v4n3.p277-288